Tackling Cultural Determinants of Health Through Nutrition Education Among Refugees (Mary Ann Liebert, 2021)
Nutrition education provides an avenue to address nutrition behavior change needs and prevents chronic disease in refugee communities. Previous studies have consistently identified cultural uniqueness as one of the barriers to meeting the needs of the refugee communities effectively. This current perspective describes the barriers and opportunities to improve nutrition education efforts among this population while taking into account the cultural context.